THE EFFECT OF EMOTIONAL LEARNING AND INTELLIGENCE MODELS ON ACCOUNTING UNDERSTANDING (EXPERIMENTAL STUDY ON MEDAN VOCATIONAL SCHOOL (SMK) 1 STUDENT) - anggono, Anggono (International Journal of Public Budgeting, Accounting and Finance, 2019)
The research objective was to examine (1) differences in accounting understanding between students taught using the problem based learning (PBL) learning model compared with students taught using direct instruction (DI) learning models, (2) differences in accounting understanding between students who have high emotional intelligence with students who have low emotional intelligence, (3) the influence of interactions between learning models and emotional intelligence on understanding accounting. The research location is in SMK Negeri 1 Medan. The study population was all students of class 10 (X) - SMK accounting for the year 2018/2019 consisting of 144 students. Sampling uses cluster random sampling, so the study sample is 61 students. This type of research is quasi-experimental with a 2 X factorial research design 2. The collection of research data using questionnaires and learning outcomes tests. The data analysis technique uses two-way ANOVA. The results showed that (1) there was a significant difference in the understanding of accounting between students taught using the problem based learning (PBL) learning model compared with students taught using the direct instruction learning model (DI). (2) There is a significant difference in the understanding of accounting between students who have high emotional intelligence and students who have low emotional intelligence. (3) There is an influence of the interaction between the learning model and emotional intelligence on the understanding of accounting.